EVOLUTION OF MINERAL COMPOSITION AND STRUCTURE OF MUHARIV GRANITES THE NORTHWEST PART OF THE UKRAINIAN SHIELD - PAVLOV, G.; PAVLOVA, O.; BUBNOVA, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
The processes (such as tectonic, metamorphic and metasomatic ones) that have changed the primary mineral composition and structure of Muhariv granites of the Ukrainian Shield have been established. The mineral paragenesises formed on each stages of their pastmagmatic transformation are determined and characterized.